Characterization, Acidifying, and Antibacterial Activity of Lactic Acid Bacteria Against Spoilage Strains Present in Chicken Meat - Choukri, Soumaya; Bouigua, Hassan; Choukri, Niama; Hammouti, Belkheir; Mouniane, Yassine; Ettouil, Abdessamad; Rokni, Yahya; Ouhssine, Mohammed (ASEAN Journal of Science and Engineering, 2023)
Nowadays, through their beneficial roles, lactic acid bacteria have been used as natural additives for the formulation of several products especially in the food industry; as they reduce the pathogen load and improve the quality of fermented food. This work focuses on the technological study of five homolactic strains isolated from three fermented barley preparations belonging to three species: Lactobacillus plantarum, Pediococcus spp, and Lactococcus lactis ssp. The experiment focused on testing their acidifying activity and their antibacterial action against a range of spoilage strains isolated from chicken meat. The identification was carried out based on the study of the cultural, morphological characters and biochemical tests which revealed the presence of five strains namely: Escherichia Coli, Salmonella sp, Staphylococcus aureus, Proteus vulgaris, and Klebsiella pneumonia. The results obtained showed that the strains (SC1, SC4, and SC5) have acidifying activities, in parallel with a significant antibacterial effect compared to the other strains (SC2, SC3) whose respective values were 1.63±0.07%, 0.99±0.23% and 1.29±0.65% for SC1, SC4 and SC5. Moreover, the cell-free culture supernatant (CFCS) inhibition zones range from 19.5 ± 0.70 mm to 10.25 ± 0.35 mm.